Nuovi paradigmi spaziali per il carcere di Secondigliano - Casalbordino, Francesco; Riccardi, Sara (TeA / Teaching Architecture, 2022)
The volume collects the results of the Final Synthesis Laboratory coordinated by prof. Marella Santangelo, held in the academic year 2019/2020 as part of the fifth year of the DiARC degree course in Architecture of the University of Naples "Federico II". The students were confronted with the project of new spaces for the Secondigliano detention center in Naples. The laboratory was a space for experimentation around a complex architecture, with the aim of improving the quality of the places where the life of the prisoners takes place, but also of the different users of the prison building. In the first part, the teachers of the laboratory describe the way in which each discipline contributed to the development of the proposed theme. The second part presents the projects developed by the students recognizing three fundamental issues for the project of the spaces of the sentence: the knowledge of the functioning of the prison and its context, the way in which the architectural project can restore a public dimension to the Detention Center and finally, the importance of the spaces dedicated to the emotional relationships between prisoners and free people. The third part collects the contributions of personalities related to the prison world who interacted with the students during the course.